Accident-induced absence from work and wage ladders - Anikó Bíró; Márta Bisztray; Jo\~ao G. da Fonseca; Tímea Laura Molnár (Institute for Fiscal Studies (IFS), 2023)
How do temporary spells of absence from work affect individuals' labor trajectory? To answer this question, we augment a 'wage ladder' model, in which individuals receive alternative take-it-or-leave-it wage offers from firms and potentially suffer accidents which may push them into temporary absence. In such an environment, during absence, individuals do not have the opportunity to receive alternative wage offers that they would have received had they remained present. To test our model's predictions and to quantify the importance of foregone opportunities to climb the wage ladder, we use linked employeremployee administrative data from Hungary, that is linked to rich individual-level administrative health records. We use unexpected and mild accidents with arguably no permanent labor productivity losses, as exogenous drivers of short periods of absence. Difference-in-Differences results show that, relative to counterfactual outcomes in the case of no accidents, (i) even short (3-12-months long) periods of absence due to accidents decrease individuals' wages for up to two years, by around 2.5 percent; and that (ii) individuals end up with lower-paying employers. The share of wage loss due to missed opportunities to switch employers is between 7-20 percent over a two-year period after returning to work, whereas at most 2 percent is due to occupation switches. Our results are robust to (a) instrumenting absence with having suffered an accident, (b) exploiting the random nature of the time of the accident, and (c) within-firm matching of individuals with and without an accident and subsequent absence spell.
Keywords: J22; J23; I10; 330; wage ladder; accidents; health shocks; temporary absence from work